Analysis Reading Comprehension Questions by Using Revised Bloom's Taxonomy on Higher Order Thinking Skill ( HOTS) - Sapta Friyanti Pakpahan; Srilasima Pakpahan; Indah Dewi Sartika Purba; Jamaluddin Nasution (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study used revised blooms taxonomy on higher order thinking skills (HOTS) which aimed in identifying reading comprehension questions. It was a qualitative research. The data taken in this study was reading comprehension question by using descriptive text. The objective of this study were the students of 8th grade.The data taken in this study was reading comprehension questions by using descriptive text. The objective of this study were the students of 8th grade junior high school in SMP SWASTA TALITAKUM MEDAN. The total of the students were 12 students. The Reading comprehension question consisted of fifteen questions in the text that had used HOTS and REVISED BLOOMS TAXONOMY criterias. The result consisted of two cycles . The first cycle showed there were 6 students who scores above KKM and in second cycle there were six students who scores under the KKM. From the result was found there were no increase and decrease of the fulfillment scores from the students and the average scores were balance. HOTS oriented English learning could increased student analyze, evaluate and create the reading comprehension questions  by using Revised BLOOMS TAXONOMY ON HIGHER ORDER THINKING SKILL (HOTS)